(untitled) (Medico Legal Update, 2021)
Introduction: Healthcare waste are considered infectious and hazardous. It requires specific handling prior to its disposal and poses a stern dangers to ecological, occupational and public health if not managed with caution. Hazardous waste management is a concern for every health care organization and for every healthcare professional. Objective: The objective of the study was to know association demographic social determinants, working status, knowledge and attitude with practice of disposal infectious waste among health personal in hospital Province of Bengkulu Methodology: A quantitative descriptive cross-sectional Study design was used. The research was carried for the period of five months from February 2019 to August 2019 and the sample size is estimate base on the multiple logistic regressions. Result: In this study, most of the respondents (42.06%) not good practice of disposal infectious waste. The multivariate analysis reported age (Adjusted OR: 1.44, 95% CI: 1.04 to 2.01) with p-value: <0.030, education (Adjusted OR: 1.40, 95% CI: 1.04 to 1.90) with p-value: <0.028, management system (Adjusted OR: 5.24, 95% CI: 3.04 to 9.03) with p-value: <0.001, knowledge (Adjusted OR: 1.85, 95% CI: 1.30 to 2.63 with p-value: <0.001, attitude (Adjusted OR: 5.21, 95% CI: 3.06 to 8.86) with p-value: <0.001. Conclusion: Almost half of hospital health personal had poor practice of disposal handling infectious waste in Bengkulu Province, Indonesia. Infectious waste management system was strongly influence on practice disposal waste.